Yes-Associated Protein 1: Role and Treatment Prospects in Orthopedic Degenerative Diseases - Xie, Wenqing; Xiao, Wenfeng; Tang, Kun; Zhang, Liyang; Li, Yusheng (Frontiers in Cell and Developmental Biology, 2020)
The Hippo/yes-associated protein 1 signalling pathway is an evolutionarily conserved signaling pathway. This signaling pathway is primarily involved in the regulation of stem cell self-renewal, organ size and tissue regeneration by regulating cell proliferation, differentiation and apoptosis. It plays an important role in embryonic development and tissue organ formation. Yes-associated protein 1 (YAP1) is a key transcription factor in the Hippo signalling pathway and is negatively regulated by this pathway. Changes in YAP1 expression levels affect the occurrence and development of a variety of tumours, but the specific mechanism associated with this phenomenon has not been thoroughly studied. Recently, several studies have described the role of YAP1 in osteoarthritis (OA). Indeed, YAP1 is involved in orthopaedic degenerative diseases such as osteoporosis (OP) in addition to OA. In this review, we will summarize the significance of YAP1 in orthopaedic degenerative diseases and discuss the potential of the targeted modulation of YAP1 for the treatment of these diseases.